Investigation of a Stand-Alone Online Learning Module for Cellular Respiration Instruction - Eric E. Goff (American Society for Microbiology, 2018)
With the recent rise of alternative instructional methodologies such as flipped classrooms and active learning, many core concepts are being introduced outside of the classroom prior to scheduled class meeting times. One popular means for external concept introduction in many undergraduate biology courses is the use of stand-alone online learning modules. Using a group of four large introductory biology course sections, we investigate the use of a stand-alone online learning module developed using animations from Virtual Cell Animation Collection as a resource for the introduction of cellular respiration concepts outside of the classroom. Results from four sections of introductory biology (n = 629) randomized to treatments show that students who interacted with the stand-alone online learning module had significantly higher normalized gain scores on a cellular respiration assessment than students who only attended a traditional lecture as a means of concept introduction (p < 0.001, d = 0.59). These findings suggest a superior ability to convey certain introductory cellular respiration topics in a stand-alone manner outside of the classroom than in a more traditional lecture-based classroom setting.